Rupture of ectopic pregnancy in rudimentary horn of uterus at 20 weeks of gestation - Haseeb, Yasmeen Akhtar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ectopic pregnancy is a well-known complication in early pregnancy .the commonest site is ampullary region of fallopian tube but sometime presentations at rare sites like rudimentary uterine horn can also happen. These rare presentations are difficult to diagnose and needs high index of suspicion on behalf of obstetrician. A 28 years old Saudi female patient with previous cesarean delivery in her second pregnancy at 20 weeks presented to the emergency department of medicine with severe abdominal pain, nausea, vomiting, dizziness and breathlessness. She was investigated on lines of pulmonary embolism but it was all inconclusive. Obstetrics & gynaecology department was consulted regarding the status of her pregnancy. On examination she was hypotensive and distended abdomen. Clinical and sonographic examination was going with internal bleeding in pelvis. Uterus was seen as separated from the fetus which was floating in free fluid in pouch of Douglas and measurements were going with 20 weeks of gestation. Initial suspicion was scarred ruptured ectopic pregnancy. The patient was immediately shifted to theatre and laparotomy performed with removal of blood and blood clots in abdomen and pelvis, an accessory horn on right side of uterus with a rent on posterior aspect noted and horn was excised. Patient recovered well and received 8 units of packed RBCs, FFP.